2001
DOI: 10.1063/1.1403667
|View full text |Cite
|
Sign up to set email alerts
|

Ge/Si interdiffusion in the GeSi dots and wetting layers

Abstract: The Ge/Si interdiffusion in GeSi dots grown on Si (001) substrate by gas-source molecular beam epitaxy is investigated. Transmission electron microscopy images show that, after annealing, the aspect ratio of the height to base diameter increases. Raman spectra show that the Si–Ge mode redshifts and the intensity of the local Si–Si mode increases with the increase of annealing temperature, which suggests the Ge/Si interdiffusion during annealing. The photoluminescence peaks from the dots and the wetting layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
3
12
0
1
Order By: Relevance
“…The catalysts as preferential sites absorb the SiO x source to reach supersaturation and then the SiO x nanowires precipitate from the catalysts to form entire nanowire [44]. To determine the possible mechanism for our case, we note that if the oxidation occurs at the former scenario, the oxide nanowires should contain Ge, since GeSi intermixing is significant at high temperature [45,46]. The fact that no Ge can be detected from the synthesized nanowires (confirmed by both EELS and EDS) suggests that our SiO x nanowires should be directly formed from the Ge-Si alloy droplets, that is, the SiO x nanowire growth should be governed by the latter scenario.…”
Section: Resultsmentioning
confidence: 96%
“…The catalysts as preferential sites absorb the SiO x source to reach supersaturation and then the SiO x nanowires precipitate from the catalysts to form entire nanowire [44]. To determine the possible mechanism for our case, we note that if the oxidation occurs at the former scenario, the oxide nanowires should contain Ge, since GeSi intermixing is significant at high temperature [45,46]. The fact that no Ge can be detected from the synthesized nanowires (confirmed by both EELS and EDS) suggests that our SiO x nanowires should be directly formed from the Ge-Si alloy droplets, that is, the SiO x nanowire growth should be governed by the latter scenario.…”
Section: Resultsmentioning
confidence: 96%
“…At present, the in uence of di erent interconnected QDs parameters (such as QD size, strain and composition in QDs) on the properties of QDs has been studied. While structural parameters (QD size and shape) have been determined by direct methods such as transmission electron microscopy (TEM), scanning tunnelling microscopy (STM) and atomic force microscopy (AFM) [3][4][5][6] optical techniques (photoluminescence and Raman spectroscopy) have been applied to study electron and vibrational spectra which provide information on strain and composition of the structures [7][8][9][10]. Evaluation of strain and composition in Ge/Si QD structures using Raman spectroscopy is based on the dependence of Ge, GeSi and Si-Si optical phonons vs. strain tensor components and composition found for Ge/Si superlattices and Ge x Si 1−x solid solutions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This will be particularly enhanced under the strain fields induced by a heteroepitaxial process. It has been suggested that the strain stored during the growth of Ge on Si substrates could significantly increase the atom mobility in the sub-surface region [81][82][83][84][85]. Some experimental observations indicate that interstitial-mediated interdiffusion could be much faster in the presence of high strain fields, because of an increased flexibility in accommodating interstitials via local deformations of the lattice [86].…”
Section: Diffusion Barriers and Kinetic Pathwaysmentioning
confidence: 99%